2017
DOI: 10.1364/ao.56.000g59
|View full text |Cite
|
Sign up to set email alerts
|

Mirages at Lake Geneva: the Fata Morgana

Abstract: Fata Morgana mirages are frequently seen at Lake Geneva. We show the first photographs of them, including a real-time video, and explain their main features, which are due to the very turbulent entrainment zones of capping inversions, especially in valley circulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
0
15
0
7
Order By: Relevance
“…Young and Frappa () write that on Lake Geneva superior mirages are common on warm and calm afternoons of sunny spring days . In San Francisco, Zinkova () has observed superior mirages on very warm and very calm days, when offshore wind brings warm air towards much colder ocean.…”
Section: Could An Arctic High Have Provided the Conditions Needed To mentioning
confidence: 99%
See 1 more Smart Citation
“…Young and Frappa () write that on Lake Geneva superior mirages are common on warm and calm afternoons of sunny spring days . In San Francisco, Zinkova () has observed superior mirages on very warm and very calm days, when offshore wind brings warm air towards much colder ocean.…”
Section: Could An Arctic High Have Provided the Conditions Needed To mentioning
confidence: 99%
“…Maltin () has suggested that a very special mirage might have been present at the site of the Titanic disaster – a Fata Morgana of the sea surface (Figure ), also known as a ‘ Fata Brumosa’ (Young and Frappa, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ducted mirages of terrestrial objects are reported in many places around the world (Young and Frappa, ), while ducted mirages of astronomical objects, such as the sun, are much rarer. The author is aware of only two publications describing the Novaya Zemlya effect mirage outside polar regions: one off Cape Town, and one off Finland (see Young’s Annotated bibliography of mirages, green flashes, atmospheric refraction, etc .…”
Section: Resultsmentioning
confidence: 99%
“…Could an Arctic high have provided the conditions needed to produce a temperature inversion? Young and Frappa (2017) write that on Lake Geneva superior mirages are common on warm and calm afternoons of sunny spring days. In San Francisco, Zinkova (2009) has observed superior mirages on very warm and very calm days, when offshore wind brings warm air towards much colder ocean.…”
Section: 'Flattened Out' Smoke -Was This a Sign Of A Temperature Invementioning
confidence: 99%
“…In most situations, when a fog arrives, the mirage leaves, but sometimes the mirage stays just a little bit longer to play the same joke with the fog as it does with everything else (Figure 2). Maltin (2012) has suggested that a very special mirage might have been present at the site of the Titanic disaster -a Fata Morgana of the sea surface ( Figure 4), also known as a 'Fata Brumosa' (Young and Frappa, 2017).…”
Section: Introductionmentioning
confidence: 99%